2018
DOI: 10.1021/acs.jctc.7b01240
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Analysis of the Spectroscopic Properties of Oxyluciferin and Its Analogues in Water

Abstract: Firefly bioluminescence is a quite efficient process largely used for numerous applications. However, some fundamental photochemical properties of the light emitter are still to be analyzed. Indeed, the light emitter, oxyluciferin, can be in six different forms due to interexchange reactions. In this work, we present the simulation of the absorption and emission spectra of the possible natural oxyluciferin forms in water and some of their analogues considering both the solvent/oxyluciferin interactions and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…All the data presented up to this point is based on the time dependent (TD) density functional theory (DFT) calculations with the range‐separated ωB97X exchange‐correlation functional. While (TD)DFT has been widely adopted due to its computational efficiency and relatively good reliability, one may criticize its use for characterizing reaction free energies as it does not properly describe the multi‐configurational characters associated with bond breaking and bond formation . Of course, this is a separate issue from the use of the range separated functional for handing charge transfer states .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the data presented up to this point is based on the time dependent (TD) density functional theory (DFT) calculations with the range‐separated ωB97X exchange‐correlation functional. While (TD)DFT has been widely adopted due to its computational efficiency and relatively good reliability, one may criticize its use for characterizing reaction free energies as it does not properly describe the multi‐configurational characters associated with bond breaking and bond formation . Of course, this is a separate issue from the use of the range separated functional for handing charge transfer states .…”
Section: Resultsmentioning
confidence: 99%
“…OLU can exist in six different chemical forms through keto/enol tautomerization combined with the deprotonation of both phenol and enol forms (Scheme ). Quite naturally, different chemical species will have different emission energies . The condition that each species prefers will also be different.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated good agreement between experimental absorption and emission spectra and calculated ensemble spectra for oxyluciferin and its analogues. [136,137] In these systems, the spectral lineshape is dominated by solute-solvent interactions and low frequency motions of the chromophore, such as twisting around a dihedral angle, which often correspond to anharmonic regions of the potential energy surface. In systems where contributions from configurations on anharmonic areas of the potential energy surface have a much stronger spectral contribution than vibronic effects, an ensemble approach based on explicit solvent representation and vertical excitation energies can yield accurate lineshapes.…”
Section: Successes and Challengesmentioning
confidence: 99%
“…For that reason, oxyluciferin analogues have been proposed and synthesized for inhibiting certain forms . In this work, we are interested in a particular set of analogues (Figure , right), studied both experimentally and theoretically . In a nutshell, such analogues are meant to avoid any keto‐enol tautomerization.…”
Section: Introductionmentioning
confidence: 99%